2022
DOI: 10.3389/fendo.2022.834978
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Outcomes in Individuals With Type 1 and Type 2 Diabetes

Abstract: ObjectiveTo determine the prevalence of neuropsychological outcomes in individuals with type 1 diabetes compared to individuals with type 2 diabetes or without diabetes, and to evaluate the association of diabetes status and microvascular/macrovascular complications with neuropsychological outcomes.Patients and MethodsWe used a nationally representative healthcare claims database of privately insured individuals (1/1/2001-12/31/2018) to identify individuals with type 1 diabetes. Propensity score matching was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(47 reference statements)
1
3
1
Order By: Relevance
“… 21 Furthermore, a single study found heart rate variability CAN outcomes, associated with cognition. 22 In contrast, we were surprised neuropathy did not associate with cognitive function, despite a previously documented relationship, 6 possibly from a lack of statistical power in the present study. The underlying mechanisms dictating the relationship between cognitive impairment, CAN, and CKD remains unknown.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“… 21 Furthermore, a single study found heart rate variability CAN outcomes, associated with cognition. 22 In contrast, we were surprised neuropathy did not associate with cognitive function, despite a previously documented relationship, 6 possibly from a lack of statistical power in the present study. The underlying mechanisms dictating the relationship between cognitive impairment, CAN, and CKD remains unknown.…”
Section: Discussioncontrasting
confidence: 94%
“…We found that CAN and CKD measures associated with smaller gray matter volumes and increased WMH, consistent with our recent study based on a large cohort of individuals with and without T2d, which found that diabetes complications increased the odds of a cognitive disorder by 2.45 in those aged 40–60 years 6 . Our results are also consistent with a systematic review that found cognitive impairment was common in individuals with CKD, 20 although in a separate study of American Indians of the Zuni Pueblo, CKD measurements did not associate with cognition 21 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations